2017
DOI: 10.1158/1078-0432.ccr-17-0955
|View full text |Cite
|
Sign up to set email alerts
|

MSH2 Loss in Primary Prostate Cancer

Abstract: Purpose Inactivation of mismatch repair (MMR) genes may predict sensitivity to immunotherapy in metastatic prostate cancers. We studied primary prostate tumors with MMR defects. Experimental Design 1133 primary prostatic adenocarcinomas and 43 prostatic small cell carcinomas (NEPC) were screened by MSH2 immunohistochemistry with confirmation by next-generation sequencing (NGS). Microsatellite instability (MSI) was assessed by PCR and NGS (mSINGS). Results Of primary adenocarcinomas and NEPC, 1.2% (14/1176)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
146
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 130 publications
(169 citation statements)
references
References 54 publications
(80 reference statements)
10
146
0
2
Order By: Relevance
“…This has been associated with underlying somatic and germline defects in MMR family constituents (hMSH2, hMSH6, hMSH3, hMLH1, hPMS1 or hPMS2) and is characterized by microsatellite instability (MSI). Besides, inactivation of MMR genes has been shown to predict sensitivity to immunotherapy in metastatic PC, similar to that seen in colorectal carcinoma (CRC) [13,14].…”
Section: Dna Mismatch Repair Systemmentioning
confidence: 84%
“…This has been associated with underlying somatic and germline defects in MMR family constituents (hMSH2, hMSH6, hMSH3, hMLH1, hPMS1 or hPMS2) and is characterized by microsatellite instability (MSI). Besides, inactivation of MMR genes has been shown to predict sensitivity to immunotherapy in metastatic PC, similar to that seen in colorectal carcinoma (CRC) [13,14].…”
Section: Dna Mismatch Repair Systemmentioning
confidence: 84%
“…Among these patients, 8% (7/91) of adenocarcinomas with a Gleason pattern 5 (Gleason score, 9–10) had MSH2 loss. Additionally, two of 43 patients (5%) with neuroendocrine prostate cancer had MSH2 loss . Schweizer et al .…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports on the aggressive pathology of MSI‐high prostate cancer. Guedes et al . reported that 1.2% (14/1176) had MSH2 loss in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The detections of CD3 and CD8 in this report provided evidence for the ‘inflamed tumor’ notion, which is required for an effective immune response. Recently, Keytruda (an antibody targeting PD‐L1/PD‐1 pathway) becomes the first cancer treatment drug approved by FDA for solid tumors with microsatellite instability‐high (MSI‐H) or mismatch repair deficient (dMMR), and prostate tumors with MSH2 loss were found with a higher density of CD8 + infiltrating lymphocytes, suggesting that Keytruda may be a treatment option for patients with prostate cancer with enriched MSH2 loss . However, the small percentage (1.2%) of MSH2 loss may also explain why limited or no response activity of PD‐L1/PD‐1 blockade therapies could be observed in advance prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Keytruda (an antibody targeting PD-L1/PD-1 pathway) becomes the first cancer treatment drug approved by FDA for solid tumors with microsatellite instability-high (MSI-H) or mismatch repair deficient (dMMR), 47 and prostate tumors with MSH2 loss were found with a higher density of CD8 + infiltrating lymphocytes, suggesting that Keytruda may be a treatment option for patients with prostate cancer with enriched MSH2 loss. 48 However, the small percentage (1.2%) of MSH2 loss may also explain why limited or no response activity of PD-L1/PD-1 blockade therapies could be observed in advance prostate cancer. Nonetheless, PD-L1 + TANs may be an additional pathology feature to screen patients with prostate cancer who would benefit from anti-PD-L1/PD-1 axis therapies.…”
Section: Discussionmentioning
confidence: 99%